KAJIAN LAHAN GAMBUT SEBAGAI CALON LOKASI/TAPAK PLTN - Khusyairi, Akhmad (BERKALA FISIKA, 2014)
The utilization of nuclear technology for energy will increase significantly which will supply electricity demand in the future. Geologically, Indonesia has varied condition which imply to design, operation and emergency plan. Peat lands have specific physical and chemical natures, therefore the owner should pay attention for this site to be assessed. The general potential hazard is peat lands fire during summer season which is effected by deforestation and low level of water surface, which will influence to the plants structure integrity. The assessment method which was used is literature study. Keywords: Peat lands, NPP, nuclear, electricity